(untitled) - Fazl-e-Haq; Dr. Aamir Shehzad; Sumbal Parveen (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The present study is an attempt to analyze Anna Burn`s novel Milkman from feminist point of view. Women have always been subjugated, discriminated and enslaved throughout the world, more or less varied, in different societies. Even though in European societies it is less and mildly expressed and felt but cannot be completely relegated. This phenomenon can be clearly observed by analyzing the literature of these nations where Milkman is not an exception. The role of language is made explicit in making such discrimination and subjugation. In this study the textual discourse of the novel is analyzed critically and observed that how female are being mistreated, discriminated, subjugated and kept in a specific social context and discourse. The study also focuses on the power relationships between male and female which have been produced and reproduced through text as dominated and subjective. The study concludes that female subjectivity, discrimination and dominance are not only restricted to Asian society but are also a part of English society which is considered to be the most educated, cultured and modern society of the world.